The Current Status of Applying E-Learning Quality Standards from the Perspective of Faculty Members at Arab American University - Mousa Khalil Odeh; Abeer Mohammad Alwahaidi (University of Science and Technology, Yemen, 2021)
The study aimed to identify the current status of applying e-learning quality standards at the Arab American University from the point of view of faculty members, and to what extent average means differ according to the different demographic variables. To achieve this, the descriptive analytical method was used, and (211) members were randomly selected, who represented (45.4%) of the study population (465) faculty members working at the Arab American university. A questionnaire consisting of (39) items covering (3) dimensions (the lecturer's role in using e-learning system, the quality of e-learning system, the role of the university administration in the quality of e-learning system) was used after testing its validity and reliability. After the descriptive statistical analysis, the results showed that the average means of the study sample towards the current status of applying the quality standards of e-learning at the university received a high degree. There were also statistically significant differences in the gender variable in favor of females; in qualification in favor of PhD holders; and in experience in favor of (more than 10 years). The study concluded with a number of recommendations, including developing and innovating new methods of evaluation suitable for the e-learning system, providing all kinds of support to faculty members, and relieving the psychological stress faced during the e-learning process.